ELT TO THE BLIND LEARNERS IN SCHOOL - Rashov Oybek Sobitjon o‘g‘li (Scientific Impulse, 2023)
Teaching English to blind students is crucial, just as it is to everyone else in the world. The increasing global interest in teaching English as a second language indicates that blind people's language learning needs cannot be ignored. Teachers also face difficulties when teaching blind kids in English. Having said so there are one or two things teachers who are not trained to teach the blind may need to know before they can be an effective teacher to a blind student.